Impact of lockdown COVID-19 on metabolic control in type 2 diabetes mellitus and healthy people - Karatas, Savas (Prim Care Diabetes, 2021)
AIMS: The impact of prolonged COVID-19 lockdown on metabolic control in type 2 diabetes patients and healthy individuals has not exactly been known. We aimed to evaluate the change in body weight and metabolic control in type 2 diabetic and non-diabetic healthy subjects during the prolonged lockdown period. METHODS: Diabetic (n = 85), and age-and sex-matched non-diabetic subjects (n = 55) were included in this prospective study. Body mass index and metabolic parameters were compared between before and 6th months of lockdown. Changes in values were evaluated using the difference before and after lockdown. RESULTS: Age (54.81 ± 10.53 vs. 52.61 ± 4.88 years), gender (female, 68.2% vs. 56.4%) and, BMI (33.44 ± 6.48 vs. 31.63 ± 3.57 kg/m(2)) were similar between groups (p > 0.05). Before and after lockdown, BMI increased both in non-diabetic (0.54 ± 0.95 kg) and diabetic groups (1.91 ± 5.48 kg) (p > 0.05). Increase in HbA1c was more in diabetic than in non-diabetic groups (0.71 ± 1.35 vs. 0.02 ± 0.19%, p = 0.002). Glucose, LDL-C, and TG increased in diabetic (39.69 ± 74.69, 7.60 ± 34.33, and 58.21 ± 133.54 mg/dl, p < 0.05) whereas non significantly decreased in non-diabetic group (−0.51 ± 4.40, −3.52 ± 14.53, and −6.47 ± 41.77 mg/dl, respectively. After adjusting BMI, increase in blood glucose (p = 0.021), HbA1c (p = 0.018), and TG (p = 0.041) levels were more in diabetic than non-diabetic group. Duration of diabetes was an independent predictor of the change in HbA1c (OR: 1.2, 95% CI = 1.1–1.8, p = 0.032). CONCLUSIONS: Body weight gain was observed in type 2 diabetic patients and healthy subjects. This is the first study to show that prolonged lockdown COVID-19 pandemic worsened glucose regulation and increased TG level in diabetes mellitus independent of weight gain.